Public Library-Led Digital Literacy Training of Older Adults Living in Social Housing - Elgamal, Raghd (My University, 2025)
This thesis investigates the phenomenon of the digital divide among older adults living in social housing (65+) and the potential impact that mobile public library-led digital literacy training with socialization components has on the learning outcomes of older adult learners. Utilizing a conceptual framework based on Social Cognitive Theory (SCT) and a theoretical model of community-led digital literacy training, the study explores how the incorporation of socialization (namely, “encouragement by others” and “observational learning”) and mobile training in the delivery of public library-led digital literacy training impacts older adults’ psychological, behavioural, and benefit learning outcomes. As an exploratory investigation, this thesis utilizes a mixed methods approach to understand the utility of the delivery of on-site Android tablet training by Hamilton Public Library (HPL) to older adult learners living in social housing at their place of residence at CityHousing Hamilton (CHH). Four weekly HPL-led classroom training sessions were complemented with additional peer-to-peer (buddy) training sessions conducted on-site at CHH in a state-of-the-art Mobile User Experience Lab (MUXL). Data collection involved: i) administration of pre- and post-training questionnaires to older adult learners; ii) pre- and post-training interviews with older adult learners, CHH/HPL administrators, and an HPL instructor; iii) observations of classroom and MUXL training sessions; and iv) the collection of biometric eye-tracking and skin conductance data of older adult learners during MUXL training sessions. Both qualitative and quantitative data analysis techniques were employed as a means of triangulating research results. Findings reveal that participants view digital literacy training as more than just learning how to use a digital device (in this case, an Android tablet). Rather, participants view digital literacy training as adding value to older adult learners’ lives, especially in terms of opportunities to socialize with peer learners and learning how to use digital devices to stay connected with close others. Findings also suggest that the learning environment, learner attributes and learner behaviour collectively impact learning outcomes such as the extent to which older adults retain and utilize the training material taught. Moreover, findings indicate that a public library plays an important role in the delivery of digital literacy training to older adults living in social housing, and that the mobile delivery of such training is necessary to reach this demographic. In addition, findings suggest that gender moderates reciprocal causation effects of the learning environment, learner attributes and learner behaviour on learning outcomes. Last, results indicate a strong need for the mobile delivery of training in ways that meet older adults’ learning needs and preferences, such as the need to offer clear structured training geared towards certain skill levels (e.g., basic, advanced) and smaller cohorts over a period of more than four weeks. This thesis provides theoretical insights and practical recommendations for researchers and practitioners who are interested in the delivery of mobile, public library-led digital literacy training to older adult community members, especially those 65+ living in social housing. In addition, methodological contributions are made in terms of recognizing the value of incorporating the collection and analysis of objective biometric data to complement traditional subjective methods (e.g., use of interviews, observations, and questionnaires) traditionally utilized in training assessment research.
Keywords: Digital Literacy; Training; Public Libraries; Older Adults; Social Housing